Takhlilu su’ūbatu tarjamatu an-nash al-arabi ila al-lughah al-indūnisiyah fi al-fasl at-tsālis at-tsanawi bima’had mu’tashim billah pontianak - Rizka Anugrah; Dina Nur Alfiyah (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2021)
The purpose of yhis research is to obtain accuratae data about the translation process, find out the difficulties experienced by students in translating, and find out various steps as a solutian in overcoming difficulties in translating arabic to indonesian lenguage. This research uses qualitative research and collect data using observation, intervies and documentation techniques. And the results of this research is: 1) the arabic translations process in tsalits tsanawi grade does not translate direcly, but is first introduced to the basics of translating so that you understand, such as mastering vocabulary and arabic grammar (nahwu & shorof). Don’t forget that the teacher always motivates at the beginning of the lesson and at the end, and in the process the students are made into several groups to present or translate the reading from the result of the student’s translation. 2) the difficulties experienced by students in translating the reading are due to a luck of vocabulary, good mastery of the rules in arabic, not being able to choose the right word equivalents, being lazy in translating due to not understanding language grammar. 3) efforts that must be made to ovecome difficulties translating means getting used to translating outside of class hours, having group study discussions, and studying a lot with seniors who understand more than them. Don’t forget the students also have to practice prounouncing reading well. Increase their vocabulary, and be able to master arabic grammar.